2016
DOI: 10.1155/2016/8056302
|View full text |Cite
|
Sign up to set email alerts
|

ZnO Nanocrystals as Anode Electrodes for Lithium-Ion Batteries

Abstract: ZnO nanocrystals were synthesized via a thermal decomposition method. X-ray diffraction, transmission electron microscopy, and photoluminescence were used to investigate the composition and nanostructure of the material. Compared with commercial ZnO nanoparticles, ZnO nanocrystals showed higher lithium storage capacity and better cycling characteristics and exhibited a reversible discharge capacity of 500 mAh g−1after 100 cycles at 200 mA g−1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 39 publications
(30 reference statements)
3
10
0
Order By: Relevance
“…Accordingly, capacities as low as 22 mAh/g were retained . On the other hand, a study based on the pure ZnO anodes was strongly correlated with this study …”
Section: Resultssupporting
confidence: 83%
“…Accordingly, capacities as low as 22 mAh/g were retained . On the other hand, a study based on the pure ZnO anodes was strongly correlated with this study …”
Section: Resultssupporting
confidence: 83%
“…The gain component of ZnO Bode plot showed a resistance of 12.1 Ohms while 7.8 Ohms was recorded for ZnO:H. Lower resistance values have been reported for nano ZnO compared to commercial ZnO. This implied that the lower resistance obtained here could be a combination of the effects of size and the enhanced conductivity due to added electrons from the H-atoms [13]. Similarly, CuO showed a resistance of 16 ohms and a much more reduced resistance of 10.8 Ohms for CuO:H ( Fig.…”
Section: Resultsmentioning
confidence: 52%
“…It is a semiconductor with interesting characteristic properties similar to ZnO as both have been used as anode electrode material for lithium ion batteries (LIBs) and other applications. On the other hand, the hybrid CuO-ZnO pn junction has been used as photocatalyst for the photochemical splitting of water molecules to generate hydrogen solar fuel [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Xiao et al reported the nanostructured ZnO initial lithiation capacity of 2958.2 mAh/g (vs. Li/Li + ), however the de-lithiation capacity was only 906.7 mA (vs. Li/Li + ) which showed 30.7% coulombic efficiency [6]. Another study by Zhang also confirmed an initial coulombic efficiency of 38% (489 mAh/g/1273 mAh/g) [22]. In our study, the initial coulombic efficiency during formation of the various ZnO samples and their specific energy can be seen in Table 4.…”
Section: Electrochemical Performance Of Zno Samplesmentioning
confidence: 95%